HUBUNGAN ANTARA PRESTASI BELAJAR, MOTIVASI DAN ETOS KERJA DENGAN KINERJA PRAKTEK INDUSTRI SISWA SMK JURUSAN MEKANIK OTOMOTIF DI SAMARINDA - andu, andu; Muslim, Supari; munoto, munoto (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
Abstract The aims of Prakerin were: (1) in order that SMK students cool learn directly from world of venture/industry, by meant that they can feel the truly work world was; (2) to increase work ability; and (3) to enhance their experiences, to practice their attitude and discipline, so that after graduate, they have readiness to work approriatly with the criteria that needed for the job. It was switable with the purpose of SMK is to work immediately after graduate. The research was conducted for: (1) to know the correlation between academic achievement and Prakerin performance; (2) to know the correlation between work motivation and prakerin performance; (3) to know the correlation between work ethic and performance Prakerin; and (4) to know the correlation between academic achievement, work motivation and work ethic jointly with Prakerin performance of SMK students in Samarinda. The type of this research was Expost Facto. The population were all of the second grade of SMK majoring in automotive mechanics in Samarinda, with the samples were the second grade of SMKN 10 and SMKM 4 students in Samarinda. The data were collected by using performance assessment for Prakerin performance variable (Y), the valve of report book for academic achievement variable (X1), guestionnaire for work motivation variable (X2) and work ethic variable (X3). The data were analyzed by using statistic test of Product Moment and Double Regression. The conclutions of the research were: (1) a significant positive correlation between academic achievement and Prakerin performance; (2) a significant positive correlation between work motivation and Prakerin Performance; (3) a significant positive correlation between work ethic and Prakerin performance; and (4) a significant positive correlation between academic achievement, work motivation and work ethic jointly with Prakerin performance. The research recommended were: (1) education office of Samarinda city support that Prakerin activity of SMK; (2) part of SMK, teachers and venture/industry word as partnersip of vocational education more increase their guidance to the students, so it can be produce local human resource competitively in automotive; and (3) to other researcher, this result could be used as a reference to do the same lund of the lund of the research with another variable, that can influence the performance in Samarinda. Keywords: Performance Industry, Human Reseurce, Achievement, Motivation and Work Ethic